Modernist Communities across Cultures and Media - Wilson, Sarah, 1973-; Pollentier, Caroline (Book collections on Project MUSE., 2019)
Questioning the assumption that modernism coincided with a loss of community, Modernist Communities Across Cultures and Media seeks to recover modernism's own communal impulses. Through a transnational and transmedial lens, this volume explores the diverse ways in which modernism reconfigured the relationships between the individual and the communal.